Efeitos das condições de contorno de Neumann na eletrodinâmica escalar - Fagundes, Fábio Nascimento (2008)
We consider the effects of homogeneous Neumann boundary conditions in the scalar electrodynamics with self-interaction. We have found if the length of the finite region is small enough the scalar field develops mass, even though spontaneous symmetry breaking is not induced. As a result the vector field does not develop mass. As byproduct we have gained the Casimir energy. We also show that the physical results (mass of the scalar field and vacuum energy density) are gauge-invariant